(untitled) (Global Journal of Management and Business Research, 2022)
Coronavirus disease 2019 is a new type of respiratory disease that has been declared a pandemic. The covid outbreak has changed the way we live, and it has also changed the food and beverage service industry. The major noticeable changes are the increase in home meal Replacement, meal kits consumption, online ordering, Take out, and Drive thru, Artificial intelligence